Food Fortification Using Spray-Dried Emulsions of Fish Oil Produced with Maltodextrin, Plant and Whey Proteins - Effect on Sensory Perception, Volatiles and Storage Stability - Damerau Annelie; Mustonen Sari A.; Ogrodowska Dorota; Varjotie Laura; Brandt Waldemar; Laaksonen Oskar; Tanska Małgorzata; Linderborg Kaisa M. (MDPI, 2022)
Fortification of foods with fish oil rich in n–3 fatty acids improves the nutritional value, but creates challenges with flavor and oxidative stability, especially during storage. Pea, soy, and sunflower proteins were used in combination with whey protein or maltodextrin to encapsulate fish oil by spray-drying. The use of whey protein compared with maltodextrin as wall material improved oxidative stability of spray-dried emulsions, although the use of whey protein increased the number of observed cracks in outer shell of the particles. Non- and encapsulated oil were used in cookies and chocolates to examine flavor characteristics by generic descriptive analysis and volatile products by solid-phase microextraction with gas chromatography-mass spectrometry. A long-term storage test at room temperature was conducted to evaluate the oxidative stability of the food models. Fortification changed the texture, odor, and flavor of the food models with fishy flavor being the most impactful attribute. For both food models, use of pea protein with maltodextrin resembled attributes of control the best. Fortification and encapsulation material also affected volatile profiles of food models. Both non-encapsulated oil and whey protein formulations performed well in regard to oxidative stability for both food models. Generally, the cookie model showed more potential for fortification than the chocolate one.